Anti-Inflammatory Effects of Rebamipide Eyedrop Administration on Ocular Lesions in a Murine Model of Primary Sjögren's Syndrome - Arakaki, Rieko; Eguchi, Hiroshi; Yamada, Akiko; Kudo, Yasusei; Iwasa, Akihiko; Enkhmaa, Tserennadmid; Hotta, Fumika; Mitamura-Aizawa, Sayaka; Mitamura, Yoshinori; Hayashi, Yoshio; Ishimaru, Naozumi (PLOS ONE, 2014)
Background Topical therapy is effective for dry eye, and its prolonged effects should help in maintaining the quality of life of patients with dry eye. We previously reported that the oral administration of rebamipide (Reb), a mucosal protective agent, had a potent therapeutic effect on autoimmune lesions in a murine model of Sjögren's syndrome (SS). However, the effects of topical treatment with Reb eyedrops on the ocular lesions in the murine model of SS are unknown. Methods and Finding Reb eyedrops were administered to the murine model of SS aged 4–8 weeks four times daily. Inflammatory lesions of the extraorbital and intraorbital lacrimal glands and Harderian gland tissues were histologically evaluated. The direct effects of Reb on the lacrimal glands were analyzed using cultured lacrimal gland cells. Tear secretions of Reb-treated mice were significantly increased compared with those of untreated mice. In addition to the therapeutic effect of Reb treatment on keratoconjunctivitis, severe inflammatory lesions of intraorbital lacrimal gland tissues in this model of SS were resolved. The mRNA expression levels of IL-10 and mucin 5Ac in conjunctival tissues from Reb-treated mice was significantly increased compared with those of control mice. Moreover, lactoferrin production from lacrimal gland cells was restored by Reb treatment. Conclusion Topical Reb administration had an anti-inflammatory effect on the ocular autoimmune lesions in the murine model of SS and a protective effect on the ocular surfaces.